Sensory-motor asymmetry lateralizing in beginner basketball training - Yakovlev, B. P.; Aksarin, I. V.; Aksarin, I. Y.; Pasishnikov, A. (Teorija i Praktika fiziceskoj Kul'tury, 2018)
Many different factors and characteristics of junior athletes are taken into account and analyzed in the sports training process. The lateralization of the functional brain asymmetry in the training of junior athletes at the initial training stage is not an exception. The article summarizes findings of our multiannual studies of the functional asymmetries in beginner basketball players. The study analyzes benefits of the sensory-motor asymmetry lateralizing in the beginner basketball trainings, with the lateralizing initiatives viewed as an extra resource for the training process efficiency improvement - since the habitual underuse of the non-leading limbs is known to hamper the individual progress. Sampled for the study were 10-12 year-old beginner basketball players (n=40) trained at sport schools. The sample was split up into a Reference Group (RG) and Experimental Group (EG) of 20 people each, with the RG trained as required by the standard CYSS/ CYORSS curriculum; and the EG trained basically under the same curriculum complemented by the sensory-motor asymmetry lateralizing practices. The sensory-motor asymmetry lateralizing training model was found beneficial as verified by the EG progress in the sensory-motor asymmetry mitigating aspects.